مقارنة تطبيق نموذج التعليمي الرؤوس المرقمة معًاNumbered Heard Together)) و طولة ألعاب الفرقTeams Games Tournament) ) لترقية مهارة الكلام الى انتاج تعليم اللغة العربية للطلاب الصف الثامن المدرسة المتوسطة الحكمة الأمانة فاجيت موجوكرطا - Nur Khasanah Febriani, Halimah; Indrawati, Ninik (Assuthur: Jurnal Pendidikan Bahasa Arab, 2024)
This research was motivated by many students who were less active and creative in learning. So that their learning results become less good. To increase student activeness and creativity, the right learning model is needed. For example with cooperative learning, one type of cooperative learning model is Numbered Heads Together (NHT), Through this learning model students are expected to be responsible for their group tasks, so that there is no separation between one student and another student in one group to give and receive each other. Here researchers also use a cooperative learning model of Teams Games Tournament (TGT) type because students are expected to be active in participating in learning through cooperation between groups in answering questions in quizzes. The purpose of this study was to determine the results of arabic learning using the Numbered Heads Together (NHT) type cooperative learning model in grade VIII MTs Hikmatul Amanah students, to determine the results of mathematics learning using the Teams Games Tournament (TGT) type cooperative learning model in grade VIII MTs Hikamatul Amanah students. and to find out the difference in Arabic learning outcomes between those who use the Numbered Heads Together (NHT) type learning model with Teams Games Tournament (TGT) in grade VIII MTs Hikamtul Amanah students. This research uses quantitative research, with the type of comparative research and experiments. The study population was the entire class VIII MTs Hikmatul Amanah which amounted to 178 students. With a sample number of 33 students from class VIII A experimental class I and VIII D experimental class II. Test The results showed that the average score of Arabic learning outcomes using the Numbered Heads Together (NHT) type cooperative learning model was 88.33 in the high category, while the average score of Arabic learning outcomes using the Teams Games Tournament (TGT) type cooperative learning model was 85.18 in the high category. The results of the hypothesis calculation obtained the value of tcalculate = 1.671 then the value was compared with the value of ttabel = 1.55 at the level of significance 0.05 Thus tcalculate > ttable. So it can be concluded "There are differences in mathematics learning outcomes between those using the Numbered Heads Together (NHT) type learning model and Teams Games Tournament (TGT) in grade VIII MTs Hikmatul Amanah students for the 2022/2023 school year".